Kosovo Country Report : Findings from the Skills towards Employment and Productivity Survey - World Bank Group (World Bank, Washington, DC, 2019)
This report provides new empirical insights into skill levels in Kosovo, based on two recent surveys. The Skills Towards Employment and Productivity (STEP) initiative of the World Bank has developed household-level and firm-based surveys to provide policy-relevant information on skills from both the supply and demand side. Household-level surveys measure the supply and use of skills in the adult urban population in a comprehensive way, including cognitive and socio-emotional skills that affect work-place readiness and effectiveness. Firm-level (employer) surveys focus on identifying the cognitive and socio-emotional job-related skills that employers seek, skills that are difficult to find, and linkages between firms and education systems.